Interface matters: Design of an efficient α-Ag2WO4/Ag3PO4 photocatalyst - Trench, Aline B.; Alvarez, Roman; Teodoro, Vinícius; da Trindade, Letícia G. [UNESP]; Machado, Thales R.; Teixeira, Mayara M.; de Souza, Daniele; Pinatti, Ivo M. [UNESP]; Simões, Alexandre Z. [UNESP]; Gobato, Yara Galvão; Andrés, Juan; Longo, Elson (Elsevier, 2022)
Heterojunction engineering of complex metal oxides is an active area of research that addresses fundamental questions in solid-state systems with broad technological applications. In this work, α-Ag2WO4/Ag3PO4 heterojunctions with different amounts of α-Ag2WO4 (12, 24, and 36 wt%) were synthesized by the coprecipitation method and characterized by X-ray diffraction, X-ray photoelectron spectroscopy, field emission scanning electron microscopy, transmission electron microscopy, UV–vis diffuse reflectance spectroscopy, and photoluminescence. The α-Ag2WO4/Ag3PO4 heterojunction containing 24% wt of α-Ag2WO4 showed the most enhanced photocatalytic activity for the degradation of Rhodamine B, being much higher than Ag3PO4 and α-Ag2WO4. Trapping experiments revealed that the holes and superoxide radical, in minor extent, were the main active species in the photocatalytic degradation. Such enhanced photocatalytic performance was explained by the surface plasmon resonance effect associated with the presence of metallic Ag at the interface and the formation of a type I heterojunction between α-Ag2WO4 and Ag3PO4 semiconductors.
Keywords: Photocatalytic activity; Surface plasmon resonance; Type I heterojunction; α-Ag2WO4/Ag3PO4